THE ESSENCE AND IMPORTANCE OF ETHICS - Kulmurodov Sardor; Mustafayev J.Sh. (Лучшие интеллектуальные исследования, 2024)
Abstract: Ethics is a philosophical science that studies the moral aspects of human behavior and provides a deeper understanding of concepts such as right and wrong, good and bad.